Cultivating food or cultivating citizens? On the governance and potential of community gardens in Amsterdam. Issue 3 (3rd March 2020) - Bródy, Luca Sára; de Wilde, Mandy
ABSTRACT: A renaissance of community gardening is unfolding on a global urban scale. Scholars have analysed community gardening projects as empowering, contested or controlled spaces depending on the local governance networks in which, or despite of which, they emerge. Focusing on the political-economic context in which gardening activities emerge in Amsterdam, we present community gardens as places where the neoliberal localisation of the city unfolds. Based on a qualitative study of 19 community gardening projects in the city of Amsterdam, we argue that community gardening projects in Amsterdam can be seen as "controlled space" [Eizenberg, E. 2012a. "Actually Existing Commons: Three Moments of Space of Community Gardens in New York City." Antipode 44 (3): 764–782.]: a space where various institutional governance actors have a varied level of influence and control. Following [McClintock, N. 2014. "Radical, Reformist, and Garden-Variety Neoliberal: Coming to Terms with Urban Agriculture's Contradictions." Local Environment 19 (2): 147–171.] who argues that community gardens can be "radical and neoliberal at once" we unpack this notion of controlled space. We compare differently managed gardening projects and describe the varied relations between gardeners and four governance actors, namely local government, welfare organisations, green NGOs and housing associations. We show how these relations both impair and enable the civic participation of gardeners, the inclusive potential of gardens and an alternative, local food provision and distribution. Finally, we reflect on what this means for the potential of community gardening, a rising urban phenomenon, to (re)claim urban space.